Pengaruh Ukuran Perusahaan, Kebijakan Dividen, dan Kinerja Keuangan terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Putri, Dita Ayuningtias Salvina; Warsitasari, Wahyu Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of company size, dividend policy and financial performance on the value of companies listed on the Indonesia Stock Exchange in 2017-2021. This study uses a quantitative approach to the type of research used, namely associative. For sampling using purposive sampling, so that after being selected obtained 16 companies with as many as 80 samples as objects of observation. The analysis technique used is panel data regression analysis with eviews 10 software tools. The results of this study indicate that simultaneously firm size, dividend policy and financial performance have a significant effect on firm value. While the results of the partial test show that company size, dividend policy and financial performance have a significant effect on firm value. Keywords: company size, dividend policy, financial performance, firm value.